2020
DOI: 10.1002/cti2.1113
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the efficacy of cytokine‐induced killer cell immunotherapy combined with first‐line chemotherapy in patients with metastatic colorectal cancer

Abstract: Objectives Fluoropyrimidine‐based chemotherapy regimens are the current first‐line treatment for metastatic colorectal cancer (mCRC); however, the outcome is often unsatisfactory. The present study aimed to determine the effect of combined cytokine‐induced killer (CIK) cell immunotherapy and first‐line chemotherapy in patients with mCRC. Methods This retrospective study included 252 patients with mCRC treated with first‐line chemotherapy. Among them, 126 patients received first‐line chemotherapy only (control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 40 publications
(87 reference statements)
0
39
0
Order By: Relevance
“…These findings, showing that postoperative CIT treatment could significantly prolong OS and PFS and reduce the rate of metastasis and recurrence in CRC patients, were consistent with results in patients with ovarian cancer, non-small lung cancer, triplenegative breast cancer, gastric cancer and liver cancer, as well as in patients with CRC metastases. [20][21][22][23][24][25][26] Subgroup analyses showed that, compared with chemotherapy alone, CIT improved the OS and PFS in CRC patients with stage II, but not stage III/ IV. Moreover, CIT treatment was more effective than chemotherapy alone in CRC patients at advanced T (T3/T4) and earlier N (N0) stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, showing that postoperative CIT treatment could significantly prolong OS and PFS and reduce the rate of metastasis and recurrence in CRC patients, were consistent with results in patients with ovarian cancer, non-small lung cancer, triplenegative breast cancer, gastric cancer and liver cancer, as well as in patients with CRC metastases. [20][21][22][23][24][25][26] Subgroup analyses showed that, compared with chemotherapy alone, CIT improved the OS and PFS in CRC patients with stage II, but not stage III/ IV. Moreover, CIT treatment was more effective than chemotherapy alone in CRC patients at advanced T (T3/T4) and earlier N (N0) stage.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, this combination was associated with few side effects, such as fever, fatigue and myalgia. 26 Although several clinical studies have assessed the efficacy of CIK cell treatments, less is known about the clinical indications for these treatments or factors, especially the molecular biomarkers, predictive of their long-term efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…evaluated the relationship between the percentage of CD3+CD56+ subset in CIK cells and survival of treated metastatic CRC patients and showed that no significant differences were observed in the OS and progression-free survival (PFS) in higher ratios of CD3+CD56+ subset in the first cycle. However, after the fourth cycle, the increase in the CD3+CD56+ subset was associated with improved OS and PFS [ 25 ].…”
Section: The Phenotype Of Cik Cellsmentioning
confidence: 99%
“…In subgroup analysis, in patients with metastatic colon cancer and patients with one metastatic site, CIK therapy significantly prolonged PFS and OS. In both studies mentioned above, no severe side effects were observed among CIK therapy patients [ 23 , 25 ].…”
Section: Clinical Studies On Cik Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation